Dynamic modelling & intelligent control of a flying machine - Woon, Hermann Wei Rong (2015)
This report documents the Final Year Project (FYP) entitled Dynamic Modelling & Intelligent Control of an Unmanned Aerial Vehicle (UAV) as part of fulfilment for the requirement for the Electrical and Electronics Engineering course. The report details the design and construction of a suitable quadcopter UAV. The UAV shall be capable of performing specific missions such as flying through high turbulence, crossing narrow space, payload delivery, passing through chain curtain, intelligence gathering and navigate through vegetation. Extensive studies and researches into the various types of UAVs, their capabilities and construction were made for the defined mission. A quadcopter UAV was selected for design and construction. The UAV is remotely controlled from a Ground Station. The UAV was designed with onboard computers and a ground station to provide an extensive and intensive processing power. This high processing power enable the mission, such as dropping of payload on target, to be pre-planned and automated, thus allowing the pilot to concentrate on the heavy workload of flying the UAV. The cardinal proper weight distribution of the UAV was achieved through a weight and balance analysis of the UAV. The UAV undergone flight tuning to achieve maximum stability. Stability is one of the most important factor which makes the UAV a successful flying machine. The UAV was also designed with flight controllable capabilities such as automatic throttle control, precision payload delivery system and Kinect flight control. The stable UAV, equipped with multitude of capabilities, represented NTU and participated in the Singapore Amazing Flying Machine Competition (SAFMC) 2015 Semi-Autonomous D1 Category. The team competed with 33 other teams from different tertiary institutes. The UAV team won the various prizes and was awarded the following:  Championship Award - Runner-up (2nd Place)  Best Presentation Award - GOLD (1st Place)  Best Video Award - 2nd Runner-up (3rd Place)